Building Self-Image: Tasya Farasya's Personal Branding Strategy as a Beauty Influencer: Membangun Citra Diri: Strategi Personal Branding Tasya Farasya sebagai Beauty Influencer - Wahyu, Ana Sofiana; Nasya Avrilia Herista; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2025)
Social media has become an important platform in building personal branding in the digital era. This research aims to explore Tasya Farasya's personal branding strategy as a beauty influencer through a descriptive qualitative approach using Social Identity Theory. The research method was conducted through in-depth observation of Tasya Farasya's social media content on Instagram, YouTube, and TikTok platforms. The results showed that Tasya succeeded in building a strong personal branding through several main strategies, namely specialisation in beauty, consistency of content, active interaction with followers, honesty, and optimal use of social media. Analysis using the concepts of categorisation, identification and intergroup comparison in Social Identity Theory reveals how Tasya constructs her identity as an influential beauty influencer. This research provides an in-depth insight into the formation of personal branding on social media and the potential of individuals in building an authentic and influential self-image.